2015
DOI: 10.2196/resprot.4189
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Therapeutic, Socially Assistive Pet Robot (PARO) in Improving Mood and Stimulating Social Interaction and Communication for People With Dementia: Study Protocol for a Randomized Controlled Trial

Abstract: BackgroundSocially assistive robotics is a growing area for geriatric research.ObjectiveThis single-blind, randomized controlled trial (RCT) aims to investigate the use of PARO, a therapeutic, socially assistive pet robot, in improving mood, and stimulating social interaction and communication for people with dementia in the community.MethodsFor the study, 40 community-dwelling older Chinese adults (≥60 years) with mild to moderate dementia will be recruited and randomly assigned to the PARO therapy group or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(60 citation statements)
references
References 49 publications
0
59
0
1
Order By: Relevance
“…“Communication” was the least‐expected role for robots and the topic was of some concern, as revealed by the open‐ended question. Although some robots that react to different stimuli and recognize emotions have been used therapeutically in hospitals, including the humanoid robot Pepper and the therapeutic pet robot Paro (Yu et al., ; Ishiguro & Majima, ), improvements in accurate interpretation of complex emotions are necessary in guardian‐free environments. Care robots may not facilitate communication between nurses and patients and indeed may also not aid communication among medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…“Communication” was the least‐expected role for robots and the topic was of some concern, as revealed by the open‐ended question. Although some robots that react to different stimuli and recognize emotions have been used therapeutically in hospitals, including the humanoid robot Pepper and the therapeutic pet robot Paro (Yu et al., ; Ishiguro & Majima, ), improvements in accurate interpretation of complex emotions are necessary in guardian‐free environments. Care robots may not facilitate communication between nurses and patients and indeed may also not aid communication among medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…For example, as many as 83% of individuals with dementia suffer with depression [2]; and as many as 77% suffer from anxiety [3]. These problems may ultimately result inlong-term hospitalization, increased medication use, and decreased quality of life for caregivers and patients.…”
Section: Introductionmentioning
confidence: 99%
“…Randomized controlled clinical trials with older adults showed that the company of a resident dog or the PARO robot reduced loneliness as compared to a control group who had neither [39]. Randomized controlled clinical trials in Hong Kong obtained better mood, more social interaction, and more communication in older adults with dementia after interaction with the PARO pet robot [40].…”
Section: Robots (Boost Resilience To) Counter Lonelinessmentioning
confidence: 97%
“…Introverts, for instance, may have fewer and less intense social connections but may not feel lonely. They connect in a less personal manner than extraverts do [4,31] (p. 40).…”
Section: Lonelinessmentioning
confidence: 99%